Welfare of the functional dependence elderly family caregiver: a gender perspective - Aurora Félix Alemán; Rosa María Aguilar Hernández; María Luz Martínez Aguilar; Hermelinda Ávila Alpirez; Laura Vázquez Galindo; Gustavo Gutiérrez Sánchez (Universidad de Alicante, 2012)
Family careers of the elderly dependent (CFAMD), vulnerable group susceptible to damage health condition; is aggravated by gender, as reflected in dimensions of welfare. Objective: To identify the welfare of the functional dependence elderly family caregiver with a gender perspective. Method: A descriptive, analytical and correlational study. Sample: 300 CFAMDF, Matamoros Tamaulipas, Mexico. Questionnaires: Sociodemographic and care data, Barthel Index and Quality of life, the latter with Cronbach alpha of 0.69. Chi-square and Pearson correlation coefficient tests. Results: Description of CFAMDF, women (85.0%), average age 42, married/ cohabiting (65.0%), son/daughter (61.4%), household work (66.3%), unemployed (49.3%) or income limited (50.7%). Women with more time and dedication to care as well as greater involvement in almost all dimensions of wellness. CFAMDF features: kinship (daughters) and occupation (household work) associated with dimensions of wellness. Welfare unaffected when only caring the elderly. Conclusion: CFAMDF was characterized as involvement in women with dimensions of welfare associated with older age, functional dependency and greater time caring the elderly. The CFAMDF women prevalence reflects the social conditioning of gender.